Pantak sebagai Jembatan Spiritual dalam Sistem Religi Dayak Kanayatn - Romanus Piter (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2026)
This article aims to explain the existence of Pantak in the religious system of the Dayak Kanayatn people as a spiritual bridge connecting humans with ancestral spirits. The focus of the study is to discuss the background of beliefs in Pantak, the process and types of its manufacture, the forms of rituals that accompany it, and the challenges of the sustainability of the Pantak tradition in the contemporary era. This research uses an exploratory study method with an interpretative approach, which integrates descriptive-ethnographic data and the author's cultural experience as part of the Dayak Kanayatn community. The results of the study show that Pantak was born from the belief in the continuity of the relationship between humans and ancestors after death, as well as the belief in Jubata as the source of life. This research confirms that Pantak is not just a cultural artifact, but a living religious symbol that is continuously negotiated amidst the dynamics and changes in religiosity, modern rationality, and social and cultural transformations of the Dayak Kanayatn people.